Analysis of a Serrated Ground Plane for a Low-Loss Reflectarray Antenna - Ren, Jiawei; Wang, Hongjian; Shi, Weichun; Ma, Minzheng (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A novel serrated ground plane (NSGP) for na low-loss reflectarray antenna is presented in this paper. Compared with a conventional smooth ground plane (CGP), the NSGP consists of a series of serrated elements, which can reflect the incident waves in the main beam direction, so the losses of the reflectarray can be effectively reduced. The principle and losses of reflectarray antennas are studied and analyzed. Then, a low-loss NSGP is proposed, and two design methods for the NSGP are given in this paper. Finally, a reflectarray antenna with elements arranged in a 15×15 grid is designed, simulated and measured with the NSGP and CGP respectively within the frequency from 12.88 to 13.88GHz. The results show that the reflectarray antenna with the NSGP can effectively utilize the reflected waves and has a maximum higher gain of 0.681 dB compared with the gain of the reflectarray with the CGP. This NSGP has a potential to be used in the high accurate design of the reflectarray which requires to realize beam forming, low-loss, high-efficiency, etc.